The Position of Children Resulting from Adultery (Islamic Law and Statute Perspective) - As'ad, Ali; Wardani, Maulida; Najmah, Nana Ulfatun; Harmain, Irfan; Farhan, Adhe Fadli (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
In this modern era, many people do not know about the law of children from outside marriage, they only follow the western world where the association there is free between the opposite sex, then cause attraction between the opposite sex and then have a relationship without a clear status without thinking about the consequences of their actions, both for themselves and for others. In this study, it is hoped that people understand the position of a child, whether from a legal or illegal marriage, in order to better protect themselves and others, this study was conducted by examining library materials and using the type of research approach used is library research (library research). If a child is the result of a woman's adultery, the child does not have a relationship with the father's family, either the biological father, and the biological father cannot provide inheritance and become the child's guardian. The child only has a blood relationship with his mother's family. But the father is still obliged to provide for his child.